Influence of shade regimes on the physiological parameters of ginger - Jayachandran, G S Sreekala, B K (Journal of Spices and Aromatic Crops, 2002)
A study was carried out at College of Agriculture, Vellayani to determine the relation of various physiological parameters on the yield of ginger under different shade levels. The experimental design was a completely randomized design with five treatments (0, 20, 40, 60 and 80 per cent shade levels) and four replications. Higher dry matter production (DMP), leaf area index (LAI), net assimilation rate (NAR) and crop growth rate (CGR) were observed in low shade level (20 per cent). The higher yield at this shade level may be due to the higher values of these physiological parameters. The results suggest a positive response of shade on the physiological parameters and yield of ginger, provided the intensity of shade is low. Regression equation fitted showed the influence of shade on DMP, NAR, CGR and yield, while no significant relation was observed with regard to LAI.